Type IV Collagen and Laminin Regulate Glomerular Mesangial Cell Susceptibility to Apoptosis Via β(1) Integrin-Mediated Survival Signals - Mooney, Andrew (American Society for Investigative Pathology, 1999)
Postinflammatory scarring is characterized by changes in extracellular matrix (ECM) composition and progressive loss of normal resident cells. In glomerular inflammation there is now evidence that unscheduled apoptosis (programmed cell death) of mesangial and other resident cells may mediate progression to irreversible glomerulosclerosis. In the current study we examined the hypothesis that ECM components may differ in their capacity to support mesangial cell survival by suppression of apoptosis. Using a well-established in vitro model of mesangial cell apoptosis, we found that collagen IV and laminin, components of normal mesangial ECM, protected rat mesangial cells from apoptosis induced by serum starvation and DNA damage, by a β(1) integrin-mediated, but arg-gly-asp (RGD)-independent mechanism. In contrast, collagen I, fibronectin, and osteonectin/SPARC, which are overexpressed in diseased glomeruli, failed to promote rat mesangial cell survival. However, the survival-promoting effect of collagen IV and laminin was not associated with changes in cellular levels of apoptosis regulatory proteins of the Bcl-2 family. These experiments demonstrate that glomerular mesangial cell survival is dependent on interactions with ECM and provide insights into potential mechanisms by which resident cell loss may occur during acute inflammation and postinflammatory scarring of the kidney and other organs.